THE ROLE OF BLOOM'S TAXONOMY IN DETERMINING PEDAGOGICAL OBJECTIVES IN THE PROCESS OF EDUCATIONAL LESSONS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Compilation of taxonomy is considered one of the important factors of increasing the efficiency of pedagogues. How quickly they will master this step, they will contribute to the acceleration of educational activities with their advanced experiences.